Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Discovery Learning Pada Pelajaran IPA Kelas IX MTsN 1 Bengkalis Tahun Pelajaran 2018/2019 - - Syafrida (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
The study aims to determine the efforts to improve science learning outcomes using the Discovery Learning model in class IX students of 1 MTsN Bengkalis in the 2018/2019. This IS action research with four stages, namely: planning, implementation, observation and reflection. The learning model used is Discovery Learning. In data collection techniques used observation, field notes, tests and documentation. The results of the application of the Discovery Learning model in class IX MTsN 1 Bengkalis can be concluded that the average value of the experiment class is increase on student learning outcomes. The improvement can be seen from the average of the class has increased namely from the results of the pre-cycle of 63.8% in the first cycle the grade average value rose to 72.2% 26 students who completed and students who did not complete 10 students 27, 7%. After repairs on the second cycle rose to 86.1%, students who complete 31 students and students who do not complete as many as 5 students 13.8%. Based on the description, it can be concluded that there is an increase in science learning achievement starting in the pre-cycle stage, cycle I and cycle II, thus the use of the Discovery Learning model can improve the science learning outcomes of class X MTsN 1 Bengkalis.